2017
DOI: 10.18632/oncotarget.19994
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophages are more resistant than M1 macrophages following radiation therapy in the context of glioblastoma

Abstract: In some highly inflammatory tumors, such as glioblastoma (GB), macrophages (MΦ) represent the most abundant population of reactive cells. MΦ, initially denoted as M0 MΦ, can be polarized into two further phenotypes: the antitumor M1 MΦ, and the protumor M2 MΦ. The three phenotypes can reside simultaneously in the tumor mass and various external factors may influence MΦ polarization. Radiotherapy is a common modality of cancer treatment aiming to target tumor cells. However, the specific effects of X-ray radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 59 publications
(85 reference statements)
0
68
1
Order By: Relevance
“…(2) TAMs that are recruited can either polarize into a continuum of macrophage states that are described with two extremes: an M1 (2a) or an M2 (2b) phenotype depending on the signal they receive (IFNg/LPS/GM-CSF for M1 and IL-4/IL-13/M-CSF for M2) Pyonteck et al, 2013;Kast et al, 2017;Roesch et al, 2018. (3) M1-like TAMs are macrophages with anti-tumor properties such as tumor cell kill abilities mediated by the production of NO, ROS, IFNg Kennedy et al, 2013;Leblond et al, 2017. They also mediate the Th1 response in the tumor through the activation of Th helper cells by secreting CXCL9, CXCL10, IL-12 Poon et al, 2017.…”
Section: Immune Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) TAMs that are recruited can either polarize into a continuum of macrophage states that are described with two extremes: an M1 (2a) or an M2 (2b) phenotype depending on the signal they receive (IFNg/LPS/GM-CSF for M1 and IL-4/IL-13/M-CSF for M2) Pyonteck et al, 2013;Kast et al, 2017;Roesch et al, 2018. (3) M1-like TAMs are macrophages with anti-tumor properties such as tumor cell kill abilities mediated by the production of NO, ROS, IFNg Kennedy et al, 2013;Leblond et al, 2017. They also mediate the Th1 response in the tumor through the activation of Th helper cells by secreting CXCL9, CXCL10, IL-12 Poon et al, 2017.…”
Section: Immune Environmentmentioning
confidence: 99%
“…TAMs participate in the induction of GB cell differentiation to a mesenchymal state through NF-kB production, an event that correlated with radiation resistance (Bhat et al, 2013). Recently, Leblond et al showed that M1 macrophages are more sensitive to radiation than M2 macrophages (Leblond et al, 2017). The proportion of M2 macrophages in irradiated tissues is thus increased.…”
Section: Tams and Radiotherapymentioning
confidence: 99%
“…8 It seems that anti-inflammatory macrophages are more radio-resistant than proinflammatory macrophages. 27 Our study clearly showed that interstitial and alveolar macrophages were modulated differently during the acute phase of IR response (Figure 1); interestingly, 15 days post-IR AMs were depleted but not IMs, suggesting that IMs are more radio-resistant than AMs. 8 Furthermore, IMs are profibrosant but not AMs.…”
Section: Macrophages Involvement In Radiation-induced Injurymentioning
confidence: 54%
“…Recently, it has been suggested that in numerous chemotherapy regimens the induction of innate and adaptive immune responses towards malignant cells significantly contribute to anti-tumor outcomes (1,17,18). Radiation-induced changes in macrophages include M2-like polarization and have been associated with disease progression (19)(20)(21). Chemotherapy also increases the immunogenicity of malignant cells and disrupts immunosuppressive circuitries in the tumor microenvironment (1,22).…”
Section: Introductionmentioning
confidence: 99%